New Insights into N-Doped Porous Carbons as Both Heterogeneous Catalysts and Catalyst Supports - Pérez Mayoral, Elena (2023)
This work was supported by project reference PID2021-126579OB-C32 from MCIN/AEI/10.13039/501100011033 and project reference UFV2023-38 from the Universidad Francisco de Vitoria de Madrid. This work also received financial support from PT national funds (FCT/MCTES, Fundação para a Ciência e Tecnologia and Ministério da Ciência, Tecnologia e Ensino Superior) through the projects UIDB/50006/2020 and 2022/05483/PTDC and the Inês Matos contract CEECIND/004431/2022. Márcia Ventura thanks FCT (Fundação para a Ciência e Tecnologia) for funding through the program DL 57/2016—Norma transitória. Publisher Copyright: © 2023 by the authors.